+0  
 
0
43
1
avatar

8(x + 5) − 2(x + 3) = 46

Guest Feb 18, 2017
Sort: 

1+0 Answers

 #1
avatar+75394 
0

8(x + 5) − 2(x + 3) = 46   simplify

 

8x + 40  - 2x - 6  = 46

 

6x + 34  = 46        subtract 34 from both sides

 

6x  = 12      divide by 6

 

x  = 2

 

 

cool cool cool

CPhill  Feb 18, 2017

15 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details